2009
DOI: 10.1111/j.1743-6109.2009.01407.x
|View full text |Cite
|
Sign up to set email alerts
|

Menopause Leading to Increased Vaginal Wall Thickness in Women with Genital Prolapse: Impact on Sexual Response

Abstract: Introduction Hypoestrogenism causes structural changes in the vaginal wall that can lead to sexual dysfunction. A reduction in vaginal wall thickness has been reported to occur after menopause, although without precise morphometry. Aim To measure vaginal wall thickness in women with genital prolapse in normal and hypoestrogenic conditions and to correlate sexual dysfunction with vaginal wall thickness and estradiol levels. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 103 publications
(125 reference statements)
1
14
0
Order By: Relevance
“…The muscular layer of the vaginal wall tends to be thicker in postmenopausal than premenopausal women, while the epithelial layer is much thinner [17]. Having developed a method to use Affymetrix arrays to read epithelial cell gene expression changes in the vagina [18], we applied this here and found down-regulation of genes involved in maintaining proliferation and barrier function of the vaginal epithelium in the dryness group.…”
Section: Discussionmentioning
confidence: 99%
“…The muscular layer of the vaginal wall tends to be thicker in postmenopausal than premenopausal women, while the epithelial layer is much thinner [17]. Having developed a method to use Affymetrix arrays to read epithelial cell gene expression changes in the vagina [18], we applied this here and found down-regulation of genes involved in maintaining proliferation and barrier function of the vaginal epithelium in the dryness group.…”
Section: Discussionmentioning
confidence: 99%
“…The vaginal wall is composed of a stratified epithelium, a lamina propria, a smooth muscle layer, and adventitia that were considered to be under the exclusive control of estrogens [26,29]. In the traditional thinking, vaginal atrophy is limited to changes in the external layer of the vagina that can be corrected by estrogens [30]. The area of the lamina propria that was markedly decreased following OVX was not completely restored by DHEA (around 69% of the value measured in intact animals).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the literature has suggested that sexual dysfunction is more common in the postmenopausal population [16], while most women undergoing POP repair fall into this age group. The application of hormone therapy may have an impact on sexual function, especially in women with the use of topical estrogen [17].…”
Section: Discussionmentioning
confidence: 99%